Facilitating Access to Justice in the Area of Economic Competition Protection - Fidria, Yuliia O.; Hofman, Yuriy B.; Demchuk, Anton M.; Andrusiak, Hanna M.; Nazaruk, Olena I. (My University, 2020)
The relevance of the study is determined by the fact that all types of competitive relations should be affected in the formation of business development programs and be based on the adoption of appropriate decisions by all parties of economic relations. The novelty of the study is determined by the fact that each of the participants in economic relations in some cases cannot receive concomitant protection, which is based on equal access to the functions and organs of justice, which are provided by public authorities as carriers of justice. The practical significance of the study is determined by ensuring fair competition to form the prerequisites for the development of the social environment.
Keywords: Justice; economics; attitude; equality; competition